Dominion over, Appropriation of, and Accessibility to Territorial Production in Alto Sinú since the Construction of the Urrá Hydroelectric Power Plant, 1994–2019 - Gómez Zárate, Patricia; Arroyave Arrubla, Sergio Iván (Universidad Pedagógica y Tecnológica de Colombia, 2020)
This article presents an analysis from critical geography on territorial production in Alto Sinú between 1994 and 2019 regarding the construction of the Urrá hydroelectric power plant. Through ethnographic research focused on territorial analysis, it identifies the planning and construction process of the hydroelectric power plant, the territorial transformations experienced by local populations, peasants, and Embera-Katíos, and the ongoing armed conflict. It was found that production in Alto Sinú derives from the interaction of three dimensions of territorial practice: dominion, appropriation, and accessibility. Dominion materializes in control measures such as legal and non-legal actions; appropriation reflects in settlement and socioeconomic organization patterns; and accessibility accounts for restrictions on certain important services such as electrical power.